Varicella‐zoster DNA in saliva of patients with meningoencephalitis: a preliminary study. (14th October 2014) - Pollak, L.; Mehta, S. K.; Pierson, D. L.; Sacagiu, T.; Avneri Kalmanovich, S.; Cohrs, R. J.
<x xml:space="preserve">Abstract</x> Objectives Since the routine use of polymerase chain reaction testing (PCR) in diagnosing herpes infections, varicella‐zoster virus is increasingly recognized as a cause of varicella‐zoster meningoencephalitis (VZV ME) among immunocompetent patients. We were interested to determine whether patients with VZV ME had VZV DNA in their saliva during the acute phase of the illness. Materials and methods Forty‐five consecutive patients who underwent a lumbar puncture for diagnostic purposes were included in the study. The cerebrospinal fluid was examined for the presence of VZV DNA by PCR, and patients with positive findings were treated with acyclovir. The saliva was later analyzed in a blinded fashion for the presence of VZV DNA. Results VZV DNA was found in saliva in four of five (80%) patients with PCR confirmed VZV ME (sensitivity 0.8, specificity 0.84, and likelihood ratio 5). This was significantly more than in patients with non‐zoster viral ME (0%, P = 0.009), parainfectious headache (12%, P = 0.03) and controls (9.5%, P = 0.007). In immunocompromised patients with systemic lymphoma and AIDS, VZV DNA was present at a similar rate (67%, P = 0.6). Conclusions We have found VZV DNA in saliva of patients with PCR confirmed VZV ME at a higher proportion than in controls and patients with non‐VZV viral ME. This finding might be of clinical importance, especially in immunocompetent individuals with suspected VZV ME where the results of genetic and immunological testing are not conclusive.